Creating a Diasporic Public Sphere in Britain: Twelver Shia Networks in London - Scharbrodt, Oliver (Islam and Christian-Muslim relations, 2020)
Since the 1980s, the Borough of Brent, in north-west London, has been a major global hub of transnational Twelver Shiism. With the influx of Iraqi refugees, many clerical leaders of Twelver Shia Islam established their European headquarters in Brent, and, in addition to Damascus and Tehran, London became a major centre of Iraqi diaspora politics during Saddam Hussein's regime. The transnational networks and organizations based in Brent engage in an Islamic transnational public space', which Bowen defines as a globally operating discursive field of Islamic reference and debate'. Based on ethnographic research in London, the article provides novel insights into the Twelver Shia Muslim organizational field in Britain and its engagement in an alternative diasporic public sphere' that articulates issues and contestations specific to Shia Muslims living in Britain: what does displacement and migration mean for Shia Muslims who have often escaped oppression, war and civil conflict; how do Shia Muslims in Britain define their relationship to Sunnis in the context of rising sectarianism in the post-Arab Spring Middle East; how do Shia Muslims position themselves towards Iran and its aspiration to be the political leader of global Shiism?